Does Development cause Economic Growth: A Perspective - Zubair, Ayesha (Université d'Ottawa | University of Ottawa, 2009)
This paper explores the empirical link between financial development and economic growth. I use data from the World Bank's World Development Indicators and the Financial Development database constructed by Thorsten Beck and Ed Al- Hussainy (World Bank). B